MANAGEMENT OF BELL PEPPER MOSAIC DISEASE COMPLEX IN HIMACHAL PRADESH - PREM N. SHARMA, SUBHASH C. CHOWFLA AND (Indian Phytopathology, 2002)
Management of bell pepper (Capsicum annuum L.) mosaic disease complex caused by viruses belonging to poty and cucumo virus groups in Solan area of Himachal Pradesh was attempted through screening of pepper germplasm and by planting of barrier/trap crops (maize, amaranth, Frenchbean and soybean). Pepper varieties Punjab Lal, Perennial and Gauhati Black, all belonging to pungent group, were found to be highly resistant to both the groups of plant viruses. Planting of maize as a barrier crop reduced the incidence of disease(s) by about 50 per cent besides increasing the yield of bell pepper.